149k views
0 votes
F(x)=4x+2 and g(x)=4(x−9)+2. What transformation occurs from function f to function g? a translation 9 units right a horizontal compression by a factor of 9 a horizontal stretch by a factor of 9 a translation 9 units down

1 Answer

5 votes

Answer:

A translation 9 units right

Explanation:

Given


f(x) = 4x + 2


g(x) = 4(x -9)+ 2

Required

Translation of f(x) to g(x)

To do this, we take the options one after the other.

A translation 9 units right

When an original function f(x) is translated to the right by h points, the resulting function g(x) is


g(x) = f(x - h)

So, we have that:


f(x) = 4x + 2

When translated to the right by 9 points,


g(x) = 4(x - 9) + 2

Hence, option A answers the question

User EchoAro
by
6.4k points